The Effect of Adding Primary Epoxy on the Corrosion Rate of Low Carbon Steel in 3.56% NaCl Solution - Ismet Eka Putra; M. Fachran Wahyudi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
The corrosion process occurs in almost all materials, especially metals, slowly but surely, which can cause a material to have a limited service life. Corrosion cannot be prevented but the rate can be reduced. One of the methods to inhibit the effective corrosion rate is by giving epoxy primer treatment. This study aims to examine the effect of adding epoxy primer on the corrosion rate of low carbon steel immersed in a 3.56% NaCl solution. This research was conducted using 27 specimens in 9 vessels, each vessel contained 3 specimens immersed in low carbon steel without treatment, oil paint and epoxy primer. Volume of 1 liter of 3.56% NaCl solution for 1 vessel. The results of this study indicate that the epoxy primer is able to inhibit the corrosion rate well. The reduction in weight of low carbon steel treated with oil paint is much greater than that of untreated low carbon steel using epoxy primer. The lowest corrosion rate was given by applying epoxy primer in 20 days of immersion with an average value of 0.0003761136666 mpy and the highest corrosion rate with paint treatment in 10 days of immersion with an average value of 0.004513367 mpy.